Waste diagnosis in public dental facilities in Recôncavo Baiano county: contributions to integrated waste management - de Oliveira Cravo Teixeira, Ana Conceição; Rolim Borges-Paluch, Larissa; Blaszkowski de Jacobi, Cláudia Cecília (O Mundo da Saúde, 2017)
Health Care Service Waste (HSW) plays an important role in public health due to its intrinsic hazards, the presence of pathogenic organisms, and the heterogeneity of its composition. Since the incorrect disposal of HSW can cause serious damage to society and to the environment, waste management should be implemented from the moment residues are generated until their final disposal. Thus, the aim of this study was to evaluate the management process of dental waste in Family Health Units (FHUs) of a city in Recôncavo Baiano county in Bahia, Brazil. Data collection was performed by means of direct observation, pictures and written descriptions of the management process, and included a structured questionnaire answered by the dentists working in the units. Our results show that the FHUs analyzed in this study did not comply with the prescribed legal standards when dealing with dental waste. Thus, a Health Care Service Waste Managing Program needs to be implemented.